Unemployment?the statistical background - Lyon, Stanley (Statistical and Social Inquiry Society of Ireland, 1943)
Statistics relating to unemployment in this country are available from two main sources. There is first, the weekly figures published in the Press showing the number of unemployed who are seeking work and who register at the various employment exchanges throughout the country and, secondly, the figures which are obtained at the decennial Censuses of Population showing the industrial status of the whole population as to whether out of work or at work.
Symposium on Irish Social Services
Read March 5th 1943
Keywords: Unemployment; Social welfare; 314.15